Association of HLA class I and II genes with cutaneous leishmaniasis: a case control study from Sri Lanka and a systematic review. Issue 1 (December 2016) - Samaranayake, Nilakshi; Fernando, Sumadhya; Neththikumara, Nilaksha; Rodrigo, Chaturaka; Karunaweera, Nadira; Dissanayake, Vajira
Abstract Background The outcome of leishmaniasis is an interplay betweenLeishamania and the host. Identifying contributory host genetic factors is complicated by the variability in phenotype, ethnicity and parasite species. Leishmaniasis is caused exclusively byL. donovani in Sri Lanka with localized cutaneous leishmaniasis (LCL) being the predominant form. We report here an association study of human leucocyte antigen (HLA) class I and II genes with LCL in Sri Lanka, the first onHLA associations in cutaneous leishmaniasis in a South Asian population. Methods An existing DNA repository of 200 each of patients and controls was typed forHLA-DQ by PCR-SSP. Next generation sequencing-based typing forHLA-A, HLA -B andHLA -DRB1 alleles was done in a subset of 280 samples. Association tests were performed on 28, 489 genotyped and imputed SNPs spanning a region of 1.4 Mb across theHLA genes. To compare our results with similar studies, we carried out a systematic review to document all HLA associations reported to-date for cutaneous and muco-cutaneous leishmaniasis. Results DRB1*04 DQB1*02 (P = 0.03;Pc = 0.09), DRB1*07 DQB1*02 (P = 0.03;Pc = 0.09) haplotypes were absent in patients.B*07 (P = 0.007;Pc = 0.13; OR = 0.36; 95 % CI = 0.17–0.77) allele andDRB1*15 DQB1*06 (P = 0.00;Pc < 0.01; OR = 0.3; 95 % CI = 0.2–.0.6) haplotype were over represented in controls andDRB1*15 (P = 0.002;Pc = 0.01) allele was over represented in patients. Two SNPs (rs281864595/rs1050517) in the antigen recognition region ofHLA-B, comprised a haplotype more frequent in controls (P = 0.04). The alleles identified by the systematic review to predispose or to protect from cutaneous/mucocutaneous leishmaniasis remained highly heterogeneous in different populations studied. Conclusions Our preliminary findings suggest a role for some class I and class IIHLA genes in determining predisposition to LCL in this population which should be corroborated with further studies. The systematic review reiterates this need, as the purported susceptibility or protection gained by certainHLA alleles or haplotypes has rarely been independently verified.